Vasectomy Simulation Curriculum and Trainer with Enhanced Face, Content and Construct Validity. Issue 3 (May 2019) - Pathak, Ram A.; Edge, Carl C.; Thomas, Garrett M.; Thiel, David D.; Broderick, Gregory A.; La Rosa, Delaney; Lannen, Amy; Moore, Monica C.; Frank, Ryan D.; Igel, Todd C.
Abstract: Introduction: We assessed the face, content and construct validity of a newly created vasectomy simulation module. Methods: Pre-simulation and post-simulation surveys quantifying simulation effectiveness, impact on confidence level and critiques of the overall design were obtained in July 2015 to assess face and content validity. Residents were subdivided based on year of residency and construct validity was ascertained via a 20-objective checklist and individual Likert score as graded by a single attending physician in a blinded fashion. Results: Two medical students and 8 residents (2 Pre-Urology, 2 Uro-1, 2 Uro-2 and 2 Uro-3) were included in the analysis. The response rate was 100% (10 of 10) for the simulation exercise and all residents (100%, 8 of 8) were used in the metric data analysis. Simulation increased the confidence to perform a vasectomy independently on average 1.58 points based on pre-simulation and post-simulation questionnaire analysis (95% CI 1.09–2.89, p=0.02). Training year had a significantly positive association (overall p <0.01) with number of objectives completed. Conclusions: Our enhanced vasectomy simulation module demonstrated excellent face, content and construct validity.